Influencing health-related behaviour with wearable cameras: strategies & ethical considerations - Doherty, Aiden; Williamson, Wilby; Hillsdon, Melvyn; Hodges, Steve; Foster, Charlie; Kelly, Paul (SenseCam '13: Proceedings of the 4th International SenseCam & Pervasive Imaging Conference, 2013)
BACKGROUND: The growing global burden of noncommunicable diseases makes it important to monitor and influence a range of health-related behaviours such as diet and physical activity Wearable cameras appear to record and reveal many of these behaviours in more accessible ways. However, having determined opportunities for improvement, most health-related interventions fail to result in lasting changes. AIM: To assess the use of wearable cameras as part of a behaviour change strategy and consider ethical implications of their use. METHODS: We examine relevant principles from behavioural science theory and consider the way images enhance or change the processes which underpin behaviour change. We propose ways for researchers to instigate the use of and engagement with these images to lead to more effective and long-lasting behaviour change interventions. We also consider the ethical implications of using digital life-logging technologies in these ways. We discuss the potential harms and benefits of such approaches for both the wearer and those they meet. DISCUSSION: Future behaviour change strategies based on self-monitoring could consider the use of wearable cameras. It is important that such work considers the ethical implications of this research and adheres to accepted guidelines and principles.